Investigation of Cronobacter sakazakii (Enterobacter sakazakii) Presence in Cereal Infant Foods - Ziver, Tevhide; Okburan, Gözde; Akgül, Özer; Saribas, Suat; Kocazeybek, Bekir; Kocazeybek, Bekir (Progress in Nutrition, 2020)
C. sakazakii is an opportunistic pathogen that may cause serious infections. Infant formulas are frequently reported as the source of infections caused by C. sakazakii. In spite of all of the taken precautions, there are recently published studies related to the isolation of C. sakazakii in formula and small children foods. In this study, we aimed to investigate the presence of C. sakazakii in cereal based infant formulas and complementary foods sold in the markets of Turkish Republic of Northern Cyprus (TRNC). We also aimed to determine the infection risk in these products. This research was carried out between May – December 2017 with the cereal-based continuing formulas and small child complementary foods of the brands offered for sale at T. R. N. C. In a total of 265 samples, including 36 varieties of cereal-based infant formula and 17 varieties of cereal-based infants and small children foods were analysed. Analysis of samples were carried out according to; ISO / TS 22964: 2006 method. C. sakazakii was not detected in any of the study samples. In conclusion, C. sakazakii was not detected in any of the cereal-based foods despite the reported detection of C. sakazakii in most of the microbiological analysis of baby foods in both the world and Turkey.